The Strength of Weak Ties You Can Trust: The Mediating Role of Trust in Effective Knowledge Transfer - Levin, Daniel Z.; Cross, Rob (Management Science, 2004)
Research has demonstrated that relationships are critical to knowledge creation and transfer, yet findings have been mixed regarding the importance of relational and structural characteristics of social capital for the receipt of tacit and explicit knowledge. We propose and test a model of two-party (dyadic) knowledge exchange, with strong support in each of the three companies surveyed. First, the link between strong ties and receipt of useful knowledge (as reported by the knowledge seeker) was mediated by competence- and benevolence-based trust. Second, once we controlled for these two trustworthiness dimensions, the structural benefit of weak ties emerged. This finding is consistent with prior research suggesting that weak ties provide access to nonredundant information. Third, competence-based trust was especially important for the receipt of tacit knowledge. We discuss implications for theory and practice.